Personal Branding Cino Fajrin through Instagram - Ayang Fitrianti; Kharisma Ayu Febriana; Firdaus Azwar Ersyad (Jurnal the Messenger, 2020)
Instagram is one of the social media that can help an account owner build personal branding, including in the context of this research, namely Cino Fajrin as one of the local celebgram with a very strong Semarangan character, and become one that stands out among other celebgrams in this city. The owner of the @cinofajrin account itself is a celebgram with 115.000 followers. The method used in this research is a case study. For the results of the study found that the formation of personal branding on Instagram as a form of specialization, leadership, personality, distinguishing, becoming visible, unity, determination, and good name. Cino Fajrin looks consistent in building personal branding on his Instagram account, allowing him to increase his 'personal' value and selling power. His success in managing branding on his Instagram account, has also led him to the opportunity to work with various event organizers, brands and companies.